Organic Anion Transporter Family: Current Knowledge - Naohiko Anzai; Yoshikatsu Kanai; Hitoshi Endou (Elsevier, 2006)
Abstract.: Organic anion transporters (OATs) play an essential role in the elimination of numerous endogenous and exogenous organic anions from the body. The renal OATs contribute to the excretion of many drugs and their metabolites that are important in clinical medicine. Several families of multispecific organic anion and cation transporters, including OAT family transporters, have recently been identified by molecular cloning. The OAT family consists of six isoforms (OAT1 - 4, URAT1, and rodent Oat5) and they are all expressed in the kidney, while some are also expressed in the liver, brain, and placenta. The OAT family represents mainly the renal secretory and reabsorptive pathway for organic anions and is also involved in the distribution of organic anions in the body, drug-drug interactions, and toxicity of anionic substances such as nephrotoxic drugs and uremic toxins. In this review, current knowledge of and recent progress in the understanding of several aspects of OAT family members are discussed. Keywords:: organic anion, p-aminohippurate, organic anion transporter (OAT), kidney